1996
DOI: 10.1159/000127116
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Growth Hormone-Releasing Factor Receptor Expression in Normal and Dwarf Rats

Abstract: Growth hormone-releasing factor (GRF) regulates GH release and somatotrope proliferation via a specific G-protein-coupled receptor. Little is known about the endocrine factors that regulate the expression of the GRF receptor (GRF-R) in the pituitary gland. We have developed a sensitive solution hybridization/RNAse protection assay for GRF-R mRNA in rat pituitary extracts. GRF-R transcripts were readily detectable in similar amounts in normal male and female rats, but were markedly reduced in extracts from age-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
4
11
0
Order By: Relevance
“…A shorter (␣) and a longer (␤) subtype of the short isoform have been distinguished; both are functional when expressed in host cells (Zeitler et al, 1998). Significant decreases in the levels of GHRH-R mRNA were reported previously in the pituitary of dw/dw rats (Carmignac et al, 1996;Zeitler et al, 1998), and the current results confirmed these observations. Findings in our laboratory suggest that GHRH binding is almost Figure 3.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A shorter (␣) and a longer (␤) subtype of the short isoform have been distinguished; both are functional when expressed in host cells (Zeitler et al, 1998). Significant decreases in the levels of GHRH-R mRNA were reported previously in the pituitary of dw/dw rats (Carmignac et al, 1996;Zeitler et al, 1998), and the current results confirmed these observations. Findings in our laboratory suggest that GHRH binding is almost Figure 3.…”
Section: Discussionsupporting
confidence: 89%
“…In adult dwarf (dw/dw) rats, plasma concentration of GH, GH content of the pituitary, and GH and cAMP responses to GHRH are greatly decreased (Charlton et al, 1988;Carmignac and Robinson, 1990;Downs and Frohman, 1991). GHRH receptor (GHRH-R) mRNA levels are reduced in the pituitary of dw/dw rats (Carmignac et al, 1996;Zeitler et al, 1998). The signal transduction pathway might also be affected distal to the receptor protein (Brain et al, 1991;Downs and Frohman, 1991).…”
mentioning
confidence: 99%
“…The quantity of the smaller of the two products ranged from 20 to 40% of the larger product based on ethidium bromide staining. Except for a decrease in the amount of product obtained from amplification of dw pituitary RNA, as recently reported (Carmignac et al 1996), there were no gross differences in the amplification products between the normal and dw pituitaries ( Fig. 1; lane 1 vs lane 2).…”
Section: Resultssupporting
confidence: 81%
“…Previous studies have described that GHRH receptors are restrictively expressed in GH cells (27)(28)(29), although we cannot exclude the possibility that low levels of receptor may be present in some other pituitary cell types. If GHRH receptors are completely restricted to GH cells, then local alterations in flow are most likely a consequence of secretory activity from stimulated GH cells.…”
Section: Discussionmentioning
confidence: 82%